Effect of artificial dawn light on cardiovascular function, alertness, and balance in middle-aged and older adults. Issue 10 (20th April 2020) - Gabel, Virginie; Miglis, Mitchell; Zeitzer, Jamie M
Abstract: Study Objectives: When arising in the morning, many older people experience dizziness and difficulty maintaining proper balance, as the cardiovascular system is not able to compensate to the postural shift (standing) and maintain sufficient blood flow to the brain. Such changes in cardiovascular function are observed in young individuals exposed to a dawn simulation light. In this study, we examined whether exposure to a dawn simulation light could impact cardiovascular function and consequent changes in balance in middle-aged and older adults. Methods: Twenty-three participants (67.3 ± 8.8 y), 12 of whom reported a history of dizziness in the morning, underwent two overnight stays in our laboratory. During both nights, they slept in complete darkness, except for the last 30 minutes of one of the nights during which a dawn simulation light was used. Continuous blood pressure (BP) and heart rate (HR) were monitored. Subjective and objective alertness, salivary cortisol, and mobile and standing balance were examined upon arising. Results: Dawn simulation light decreased (33%) the amount of sleep before morning awakening, lowered BP (6.24 mmHg), and increased HR (0.93 bpm). Despite these changes in physiology, there was no significant impact of dawn simulation on subjective or objective alertness, measures of standing or ambulatory balance, morning cortisol awakening response, or cardiovascular function after awakening. Conclusion: While the dawn simulation did cause an increase in wake and a change in cardiovascular function prior to morning arousal in older adults, we could find no evidence of a functional change in either cardiovascular function or balance upon standing. Clinical Trial: Registered on Clinicaltrials.gov, #NCT02632318, https://clinicaltrials.gov/ct2/show/NCT02632318